Investigating burnout factors among higher education teachers in Guilin, China: Implications for quality education - Hongyu, Zhou; Liu, Yang; Vijayaratnam, Phawani; Wei, Huang; Rajanthran, Subashini K (International Journal of Innovative Research and Scientific Studies, 2025)
The objective of this study is to explore the impact of transformational leadership, workload, and teacher self-efficacy on teacher burnout in universities in Guilin, and to provide administrators with strategic suggestions for reducing teacher occupational stress, improving education quality, and enhancing teacher retention. This study is based on the Bush collegial model, which emphasizes teacher participation in decision-making and equal voice, achieving organizational goals through collaboration and consensus, and improving teacher professional identity and job satisfaction, thereby effectively alleviating occupational burnout. The research adopts a quantitative method, utilizing an online questionnaire survey of teachers in three universities in Guilin, employing tools such as MBI-ES, MLQ-5X, and TSE Teacher Self-efficacy Scale to collect and analyze data on the factors influencing teacher burnout. Data from 338 respondents indicated that transformational leadership and teacher self-efficacy are negatively correlated with burnout, while workload is positively correlated. This study addresses a gap in the literature on teacher burnout in Guilin universities by applying Tony Bush’s collegial model and offers intervention strategies for university administrators to cultivate transformational leadership, optimize workload management, and enhance teacher self-efficacy, aiming to reduce burnout and improve job satisfaction and career development.